Kontruksi Spiritual Quotient dan Implikasinya dalam Belajar: Suatu Analisis Psikopedagogis - Suriana, Suriana; Walidin, Warul; Gade, Syabuddin; Mahmud, Salami (ISTIFHAM, 2024)
Spiritual quotient is the awareness and activation of faith as a natural potential in interpreting life with the value of worship which is raised through moral attitudes and behavior in a balanced and perfect manner. However, the current phenomenon is that spiritual quotient seems to be underestimated and not important to develop in the learning process. This study seeks to explore how spiritual constructs influence motivation, learning quality and personal development of individuals by considering psychological and pedagogical factors, by conducting desk research. This method allows for the collection of data from various literatures, such as books, documentary materials, magazines, journals and newspapers. This research uses a qualitative approach, which emphasizes the analysis of the comparative inference process and the dynamics of the relationship between observed phenomena. spiritual quotient can be defined as religious encouragement and stimulation which is the potential of human nature brought from birth. In the Islamic concept, spiritual quotient has 5 dimensions, namely fitrah, spirituality, tawhid, morals, and istiqamah practice. Furthermore, in the learning process, spiritual quotient can foster students' intrinsic motivation, build emotional maturity, and increase focus and calmness in students' hearts. The role of the teacher in developing this spiritual quotient is to be a role model, create a spiritually-based learning environment, integrate spiritual values, and encourage self-development.